A novel RUNX2 splice site mutation in Chinese associated with cleidocranial dysplasia - Jing Wang; Qiuying Li; Hongyu Li; Xiu Liu; Ying Hu; Yuxing Bai; Kai Yang (Heliyon)
Pathogenic genes in most patients with cleidocranial dysplasia have been confirmed to be runt-related transcription factor 2 (RUNX2), which controls mutations in specific osteoblast transcription factors and affects skull ossification and suture adhesion. This study aimed to explore the role of RUNX2 mutations. Here, we report a rare case of a splice site mutation in a Chinese population with typical cleidocranial dysplasia symptoms, cranial suture insufficiency, clavicle dysplasia, and dental anomalies. Peripheral blood samples from the proband and her mother were subjected to Sanger sequencing. The expression levels of RUNX2 before and after mutation were verified using digital PCR (dPCR). The results revealed a classic mutation at the fifth base of the intron 5 initiation splicing sequence (NM001024630.4: C.685+5G > A). The mutation rate in the proband was 53 %, while the mother did not have any mutations. The secondary RNA structure of the RUNX2 gene in the progenitor was predicted to change, and the structural free energy was low in the wild-type, with the stem folded first and the structure being relatively stable. After the mutation, the free energy increased. This finding enriches the RUNX2 mutation library of CD-related genes in Chinese individuals.